Long COVID in transgender and gender nonbinary people in the United States - Andrea L. Wirtz; Sari L. Reisner; S. Wilson Cole; Darya Adams; J. D. Davids; Alison K. Cohen; Carter Brown; Marissa Miller; Tonia C. Poteat (Scientific Reports)
Abstract Despite recommendations in the US National Research Action Plan on Long COVID, gender identity is rarely reported in research and surveillance used to guide public health programming and clinical care. We analyzed data from a cross-sectional study of COVID-19 in a nationwide sample of transgender and nonbinary (TNB) people (N = 2,134). Participants were surveyed between June 14, 2021 and May 1, 2022. Data were restricted to 817 participants who reported confirmed or suspected COVID-19 to estimate the prevalence of long COVID, defined as symptoms persisting for ≥ 3 months. Ten percent of participants with a history of COVID-19 reported symptom duration consistent with long COVID, ranging from 4.8% to 12.9% across gender identities. Long COVID was most common in transmasculine and nonbinary people assigned female sex at birth. There was no evidence of an association with reported hormone therapy, supporting current recommendations that prioritize gender-affirming care during treatment for long COVID. As a condition which profoundly impacts health and productivity, long COVID is likely to exacerbate existing disparities. Principles of equity demand that we reduce barriers to prevention, diagnosis, and care for long COVID, and ensure that research and surveillance are inclusive of TNB people and disaggregate findings by gender identity.